Analisis Yuridis Kekuatan Hukum Perjanjian Lisan Dalam Hubungan Hukum - Vivit Choirul Nisya; Indra Yuliawan (Universitas Ngudi Waluyo, 2023)
The agreement is one of the legal relations that is often carried out in social life in society. An agreement according to Article 1313 of the Civil Code is an act by which a person or more binds himself to one or more other people. Without realizing it, verbal agreements are often carried out in social life. The purpose of this paper is to determine the legal power of oral agreements in legal relations, especially accounts payable and legal relations in the settlement of receivables as a result of oral agreements. The method used by researchers in this research is descriptive qualitative. With this method the researcher wants to analyze the oral agreement in Semarang Regency which was carried out by Vicri and Daryoto. This is where Daryoto and Vicri entered into a receivables agreement where Vicri acts as Daryoto's Creditor as the Debtor. Daryoto owed a sum of money to Vicri without a letter or written statement from both parties, however the transfer of money was known to the wives of both parties and Vicri's parents. This is done on the basis of trust and kinship. Daryoto promised to pay his installments every month to Vicri, but it turned out that Daryoto was unable to fulfill his achievements. Under these circumstances it was difficult for Vicri to collect Daryoto's debt, because there was no written evidence. Article 1313 of the Civil Code contains the essence that an agreement occurs because of an agreement. Whereas Article 1320 of the Civil Code has regulated the legal terms of the agreement both formally and materially, the parties who promise to carry out the agreement that has been made must fulfill the elements of Article 1320 of the Civil Code. Therefore a request made orally if it complies with Article 1320 of the Civil Code is valid. However, when the other party denies it, in order to have legal force, it must meet the evidence in accordance with Article 1866 of the Civil Code. Oral agreements are very risky and in practice there are still many obstacles due to the difficulty of making agreements in oral agreements. Abstrak Perjanjian merupakan salah satu hubungan hukum yang kerap kali dilakukan dalam pergaulan hidup di dalam masyarakat. Perjanjian menurut Pasal 1313 KUH Perdata adalah suatu perbuatan dengan mana seseorang atau lebih mengikatkan dirinya terhadap satu orang lain atau lebih. Tanpa disadari, perjanjian lisan kerap kali dilakukan dalam kehidupan bermasyarakat. Tujuan dari penulisan ini adalah untuk mengetahui kekuatan hukum perjanjian lisan dalam hubungan hukum khusunya hutang piutang dan hubungan hukum dalam penyelesaian terhadaphutang piutang sebagai akibat dari perjanjian lisan. Metode yang digunakan peneliti dalampenelitian ini adalah deskriptif kualitatif. Dengan metode tersebut peneliti ingin menganalisiskasus perjanjian lisan di Kabupaten Semarang yang dilakukan oleh Vicri dan Daryoto. Halmana Daryoto dan Vicri melakukan perjanjian hutang piutang dimana Vicri selaku KrediturDaryoto selaku Debitur. Daryoto hutang sejumlah uang kepada Vicri tanpa surat ataupernyataan secara tertulis kedua belah pihak namun penyerahan uang diketahui oleh istri darikedua belah pihak dan kedua orangtua Vicri. Hal ini dilakukan atas dasar kepercayaan dankekeluargaan. Daryoto berjanji membayarkan angsurannya setiap bulan kepada Vicri, ternyatapihak Daryoto tidak mampu memenuhi prestasinya. Dalam keadaan demikian Vicri sulit untukmenagih hutang kepada Daryoto, karena tidak ada bukti tertulis. Dalam Pasal 1313 KUHPerdata mengandung inti bahwa perjanjian terjadi karena kesepakatan. Sedangkan dalam Pasal1320 KUH Perdata telah mengatur syarat sah perjanjian baik secara formil dan materiil makaterhadap para pihak yang berjanji untuk melakukan kesepakatan yang sudah dibuat harusmemenuhi unsur unsur Pasal 1320 KUH Perdata. Oleh karena itu perjanjian yang dibuat secaralisan bilamana memenuhi Pasal 1320 KUH Perdata termasuk sah. Akan tetapi pada saat pihaklain mengingkari maka agar memiliki kekuatan hukum harus memenuhi bukti-bukti sesuaiPasal 1866 KUH Perdata. Perjanjian lisan sangat beresiko dan dalam pelaksanaannya masihbanyak kendala-kendala karena sulitnya melakukan pembuktian dalam perjanjian lisan.